Enantioselective Sulfoxidation of Thioanisole by Cascading a Choline Oxidase and a Peroxygenase in the Presence of Natural Deep Eutectic Solvents. Issue 1 (30th January 2020) - Li, Yongru; Ma, Yunjian; Li, Peilin; Zhang, Xizhen; Ribitsch, Doris; Alcalde, Miguel; Hollmann, Frank; Wang, Yonghua
Abstract: A bienzymatic cascade for selective sulfoxidation is presented. The evolved recombinant peroxygenase from Agrocybe aegeritra catalyses the enantioselective sulfoxidation of thioanisole whereas the choline oxidase from Arthrobacter nicotianae provides the H2 O2 necessary via reductive activation of ambient oxygen. The reactions are performed in choline chloride‐based deep eutectic solvents serving as co‐solvent and stoichiometric reductant at the same time. Very promising product concentrations (up to 15 mM enantiopure sulfoxide) and catalyst performances (turnover numbers of 150, 000 and 2100 for the peroxygenase and oxidase, respectively) have been achieved. Abstract : Natural deep eutectic solvents (NADES) based on choline chloride were used as cosolvents for the bienzymatic sulfoxidation of thioanisole comprising a choline oxidase ( An ChOx) for the in situ generation of H2 O2 to promote the peroxygenase (r Aae UPO)‐catalysed, stereoselective sulfoxidation. Hence, the NADES had a double function as cosolvent and as stoichiometric reductant for the in situ H2 O2 generation. The preliminary results presented here hint towards practical usefulness of this approach.